Elas compravam, vendiam e castigavam:: mulheres brancas no sul escravista dos Estados Unidos - Carula, Karoline (Afro-Ásia, 2021)
Resenha de: JONES-ROGERS, Stephanie E. They Were Her Property: White Women as Slave Owners in the American South. New Haven: Yale University Press, 2019. 320 p.